Measuring Subjective Happiness by Newly Developed Scale in Tehran, Iran - Abachizadeh, Kambiz (Novelty in Biomedicine, 2015)
Background: Happiness as one of the main positive health indicators has drawn more attention in recent years among policy makers and health system managers. There are few studies performed to measure happiness in population-based settings in Iran. In response to this need, our study tends to assess Iranians subjective happiness in Tehran, Capital city of Iran. Materials and Methods: Present study was conducted in Tehran, Capital of Iran, with more than 7 Million populations in January 2013, using a two-step approach. In first step c conceptual framework of Iranians’ happiness was developed. In the second phase of study, a survey recruiting 700 participants was conducted. Stratified cluster sampling method was employed. Participants were recruited from all the 22 municipal divisions of Tehran as strata, proportional to the population size and its gender and age distribution. Happiness was measure by a 40-item questionnaire with scores ranged among 40 to 200. Results: Conceptual framework of Iranians’ happiness based on reviewed documents and consensus building process was the product of first step. At second step, from a pool of 700 persons, 696 (97%) agreed to participate and filled out the questionnaire completely. The mean of happiness score was 143.9 (95% confidence interval, 142.5 to 145.4). The results show that the happiness score of jobless people (135.1, 95%CI: 128.1-142.0) and widowed singles (126.6, 95%CI: 113.0-140.2) were significantly lower than other corresponding groups. There was no significant association between gender, age group, educational level as determinants and happiness. Conclusion: Happiness level of Tehranians is somewhat higher than the moderate level. This finding is consistent with findings of other conducted studies in country. However, it is not consistent with some of international reports of happiness, For instance, Happy Planet Index. Due to inadequate information, it is necessary to conduct more research to measure subjective happiness and its determinants, specially, in a nation-wide approach.